Slang language use in social media among Malaysian youths: a sociolinguistic perspective - Abdullah, Nur Nabilah; Mohd Ghazali, Norshahira (Kulliyyah of Languages & Management (KLM), 2021)
The rise of young people as social media users resulted in the creation of the world's largest virtual community, as well as the emergence of internet slang as a new linguistic form to meet the communicative demands of social networking. Because internet slang language is not standardised and may differ in different community environments, it can create communication barriers, as well as a communication gap between older and younger generations. The purpose of this study is to investigate the different types and functions of using slang language on Twitter and TikTok among Malaysian youth using a sociolinguistic approach. This study used descriptive qualitative research to identify and analyse the various types and functions of slang words used as captions on TikTok videos and Twitter tweets based on Chapman's theory. This study's findings identified 17 slang languages, eight of which are primary slang and ten of which are secondary slang, and discovered that the functions of slang languages used by Malaysian youth on TikTok and Twitter are to express something quickly and to communicate secretly so that a specific listener can understand something.